Activity of a Synthetic Peptide Targeting MgtC on Pseudomonas aeruginosa Intramacrophage Survival and Biofilm Formation - Malika Moussouni; Malika Moussouni; Pauline Nogaret; Pauline Nogaret; Preeti Garai; Preeti Garai; Bérengère Ize; Eric Vivès; Anne-Béatrice Blanc-Potard; Anne-Béatrice Blanc-Potard (Frontiers in Cellular and Infection Microbiology, 2019)
Antivirulence strategies aim to target pathogenicity factors while bypassing the pressure on the bacterium to develop resistance. The MgtC membrane protein has been proposed as an attractive target that is involved in the ability of several major bacterial pathogens, including Pseudomonas aeruginosa, to survive inside macrophages. In liquid culture, P. aeruginosa MgtC acts negatively on biofilm formation. However, a putative link between these two functions of MgtC in P. aeruginosa has not been experimentally addressed. In the present study, we first investigated the contribution of exopolysaccharides (EPS) in the intramacrophage survival defect and biofilm increase of mgtC mutant. Within infected macrophages, expression of EPS genes psl and alg was increased in a P. aeruginosa mgtC mutant strain comparatively to wild-type strain. However, the intramacrophage survival defect of mgtC mutant was not rescued upon introduction of psl or alg mutation, suggesting that MgtC intramacrophage role is unrelated to EPS production, whereas the increased biofilm formation of mgtC mutant was partially suppressed by introduction of psl mutation. We aimed to develop an antivirulence strategy targeting MgtC, by taking advantage of a natural antagonistic peptide, MgtR. Heterologous expression of mgtR in P. aeruginosa PAO1 was shown to reduce its ability to survive within macrophages. We investigated for the first time the biological effect of a synthetic MgtR peptide on P. aeruginosa. Exogenously added synthetic MgtR peptide lowered the intramacrophage survival of wild-type P. aeruginosa PAO1, thus mimicking the phenotype of an mgtC mutant as well as the effect of endogenously produced MgtR peptide. In correlation with this finding, addition of MgtR peptide to bacterial culture strongly reduced MgtC protein level, without reducing bacterial growth or viability, thus differing from classical antimicrobial peptides. On the other hand, the addition of exogenous MgtR peptide did not affect significantly biofilm formation, indicating an action toward EPS-independent phenotype rather than EPS-related phenotype. Cumulatively, our results show an antivirulence action of synthetic MgtR peptide, which may be more potent against acute infection, and provide a proof of concept for further exploitation of anti-Pseudomonas strategies.